Application of hydrothermal reactions to biomass conversion - Jin, Fangming (Green Chemistry and Sustainable Technology, 2014)
This book reviews the recent advances in hydrothermal conversion of biomass into chemicals and fuels, and consists of 15 chapters. It introduces the properties of high-temperature water, the merits of hydrothermal conversion of biomass, and some novel hydrothermal conversion processes, mainly including hydrothermal production of value-added products, hydrothermal gasification, hydrothermal liquefaction and hydrothermal carbonization. This book introduces a new concept for counteracting the imbalance in the carbon cycle, which is caused by the rapid consumption of fossil fuels in anthropogenic activities in combination with the slow formation of fossil fuels. Accordingly, the book is useful in conveying a fundamental understanding of hydrothermal conversion of biomass in the carbon cycle so that a contribution can be made to achieving sustainable energy and environment. It is also interesting to a wide readership in various fields including chemical, geologic and environmental science and engineering. Fangming Jin is a Distinguished Professor at the School of Environmental Science & Engineering, Shanghai Jiao Tong University, China